Efficacy of a Rinse Containing Sea Salt and Lysozyme on Biofilm and Gingival Health in a Group of Young Adults: A Pilot Study - Jeyaraj Hoover; Eduardo Tovar; Trevor Zlatnik; Chandima Karunanayake (Hindawi Limited, 2017)
Objectives. To evaluate new mouth rinse containing sea salt, xylitol, and lysozyme on biofilm formation and gingival health in a group of young adults. Methods. The subjects were divided into two groups of 15 subjects each: control (A) and experimental group (B). The Turesky modification of Quigley-Hein plaque index was used to evaluate plaque scores while the presence or absence of gingival bleeding was used to determine gingival health. Measurements were done at baseline and at the end of the one-month trial period by one blinded examiner on six representative teeth. Group (A) maintained standardized oral health practices for the duration of the experiment. In addition, group (B) rinsed with a tablespoon of the provided sea salt mouth rinse for 30 seconds once in the morning and at night. After the 30-day trial period, subjects in both groups were reassessed as per baseline. Results. There were no statistically significant differences in the overall reduction from baseline in the mean plaque and gingivitis scores on all surfaces or on individual surfaces. Conclusion. Within the limitations of the study, rinsing with sea salt for thirty days did not affect the gingival and plaque scores in a group of young adults.